Sharing Economy-Based Business Model Innovation: Challenges and Opportunities in the Society 5.0 Era - Amelia Amelia (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
The sharing economy has become a global phenomenon that is able to change the traditional business paradigm towards a collaboration-based model. In the context of Society 5.0, the sharing economy is not only seen as a technological innovation, but also as a human-centered society development strategy that emphasizes a balance between economic progress and social problem solving. This research aims to: (1) identify potential sharing economy business model innovations, (2) analyze implementation challenges and opportunities, and (3) formulate synergy strategies with Society 5.0. The research method used is qualitative descriptive, with data collection through in-depth interviews, observations, and documentation studies. Data analysis was carried out using Miles & Huberman's interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that innovations such as pay-per-use, peer-to-peer lending, ride sharing, and coworking space dominate the development of the sharing economy. The main challenges in implementation lie in regulations, digital literacy gaps, limited human resources, and low public trust. However, greater opportunities open up through the use of cutting-edge technology, increased digital literacy, and the implementation of adaptive regulations. The implications of this study show that with strategies to strengthen regulations, inclusive digital transformation, and increase technology-based trust, the sharing economy can be the main driving force for inclusive and sustainable economic development within the framework of Society 5.0.